Framing obesity a disease: Indirect effects of affect and controllability beliefs on weight bias. Issue 10 (October 2018) - Nutter, Sarah; Alberga, Angela; MacInnis, Cara; Ellard, John; Russell-Mayhew, Shelly
Abstract Background/objectives Obesity has been declared a disease by the American and Canadian Medical Associations. Although these declarations sparked much debate as to the impact of framing obesity as a disease on weight bias, strong empirical research is needed to examine this impact. The current study examined the impact of framing obesity a disease on weight bias, focusing on moderating and mediating processes. Subjects/methods A sample of 309 participants living in the United States or Canada was recruited from Crowdflower. Participants completed measures of demographics, ideology, general attitudes, and previous contact quality and quantity with people living with obesity. Participants then read one of three articles as part of an experimental manipulation framing obesity as a disease, obesity not as a disease, and a control article unrelated to obesity. Post-manipulation included measures of affect, disgust, empathy, blame, and weight bias. Results Orthogonal contrasts were used to compare the obesity-disease condition to the obesity-not-disease condition and control condition. The manipulation had a direct effect on affect (emotions), such that affect toward individuals with obesity was more positive in the obesity-disease condition than the obesity-not-disease and control condition combined. Exploration of moderating effects revealed that both the belief in a just world and weight satisfaction moderated the relationship between the obesity-disease manipulation and blame for obesity. Two models of indirect effects on weight bias were also examined, which demonstrated that the obesity-disease manipulation predicted less weight bias through more positive affect (model 1) as well as less weight bias through decreased blame among individuals high in belief in a just world (model 2). Conclusions This study further highlights the complex effects of declaring obesity a disease, uncovering a new direction for future research into the role of affect as well as indirect effects of characterising obesity a disease on weight bias.